Targeting interleukins for the treatment of inflammatory bowel disease-what lies beyond anti-TNF therapy? - Mclean, Mairi H.; Neurath, Markus; Durum, Scott K. (Inflammatory Bowel Diseases, 2014)
: Inflammatory bowel disease accounts for significant patient morbidity in the Western world. Several immunosuppressive therapies are available but are associated with potential significant adverse effects. In addition, there remains a cohort of patients with refractory or relapsing disease. Therefore, the search for novel therapeutic agents continues. In this review, we evaluate the role of a number of designated cytokines that are candidates in the pathogenesis of inflammatory bowel disease and discuss how their manipulation has been explored as a therapeutic strategy for this disease. The interleukins (ILs) chosen for discussion reflect those that currently show most promise as future therapeutic targets, as well as discussing the role of some of the most recently identified ILs, such as IL-27, IL-33, IL-35, and IL-22, in this context.
EVALuna2:1898